Family Support for Student Wellbeing of Migrant Students at Universitas Hasanuddin Makassar - Qisty Anindiati (PT FORMOSA CENDEKIA GLOBAL, 2024)
study aims to determine whether there is a relationship between family support and the welfare of migrant students. Knowing the level of student well being, and knowing the effective contribution of family social support to student well-being. The research subjects were 115 overseas students at Universitas Hasanuddin Makassar. The method uses a quantitative approach. The data analysis technique used in this study is the Product Moment correlation of the person. Based on the results of data analysis, the correlation coefficient was obtained as ???????????? = 0.723 with sig. = 0.000; p < 0.001, so that the proposed hypothesis is accepted, it can be said that there is a very significant positive relationship between family social support and student well-being. The effective contribution of family support to student well-being is 63.5% and the remaining 36.5% is influenced by other variables. The level of student well being of overseas students is included in the high category with an empirical mean of 69.20 and a hypothetical mean of 57.5. Family support is included in the high category with an empirical mean of 79.25 and a hypothetical mean family support scale of 62.5